A roadmap for improving the representation of photosynthesis in Earth system models. Issue 1 (January 2017) - Rogers, Alistair; Medlyn, Belinda E.; Dukes, Jeffrey S.; Bonan, Gordon; von Caemmerer, Susanne; Dietze, Michael C.; Kattge, Jens; Leakey, Andrew D. B.; Mercado, Lina M.; Niinemets, Ülo; Prentice, I. Colin; Serbin, Shawn P.; et al.
Summary: Accurate representation of photosynthesis in terrestrial biosphere models (TBMs) is essential for robust projections of global change. However, current representations vary markedly between TBMs, contributing uncertainty to projections of global carbon fluxes. Here we compared the representation of photosynthesis in seven TBMs by examining leaf and canopy level responses of photosynthetic CO2 assimilation ( A ) to key environmental variables: light, temperature, CO2 concentration, vapor pressure deficit and soil water content. We identified research areas where limited process knowledge prevents inclusion of physiological phenomena in current TBMs and research areas where data are urgently needed for model parameterization or evaluation. We provide a roadmap for new science needed to improve the representation of photosynthesis in the next generation of terrestrial biosphere and Earth system models.